The Principals of Improvement Students' Individual Work in The Period of Digital Education (Eurasian Scientific Herald, 2023)
Students still continue to learn virtually from home and in the classroom. Teachers regularly search for digital education resources to supplement curriculum and engage their students. Digital Instructional Materials, a 2020 research report, surveyed ELA, math and science teachers across the United States. It found that 95 percent of elementary teachers and 97 percent of secondary teachers use Google to help plan instruction. Plus, more than half of teachers use online educational sites to find digital resources. School districts can support teachers and help them with strategies to ensure that digital resources are used effectively.